STRATEGI PENINGKATAN PENERIMAAN PAJAK HOTEL DI KOTA SUKABUMI - Virnawati, Mitha; Hakim, Dedi Budiman; Falatehan, A Faroby (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 11 Nomor 2 Tahun 2017DO - 10.24843/MATRIK:JMBK.2017.v11.i02.p04, 2017)
Hotel tax is one of a local tax that has great potential to be increased as one source of local government revenue (PAD). Revenue from hotel tax in the City of Sukabumi is smaller when compared with other local taxes, so it needs strategies to increase its income revenue. This research included descriptive research type with using primary and secondary data. Analysis method used were growth and contribution ratio, effectiveness and efficiency ratio, and analytical hierarchy process. The purpose of this research were to determine the growth rate and the contribution of hotel  tax to local revenue, to measure the effectiveness and efficiency of hotel tax and to determine the strategies in the implementation of revenue hotel tax. The result of this research presented on average the growth of hotel tax revenue was 13.18 %. Its contribution to local taxes averaged of 3.91 %, and contribution to local government revenue averaged of 0.47 % with category is very less, the average of effectiveness rate 107.93 % so the category was very effective and the efficiency level 5.67 % so the category highly efficient. To increase the hotel tax revenues required strategies by improving the system of management and supervision, socialization and low enforcement, tourism promotion, facilities infrastructure, and quality of human resources.